Autonomy, Well-Being and the Order of Things: Gilabert on the conditions of social and global justice - Straehle, Christine (Les ateliers de l'éthique / The Ethics Forum, 2013)
Gilabert argues that the humanist conception of duties of global justice and the principle of cosmopolitan justifiability will lead us to accept an egalitarian definition of individual autonomy. Gilabert further argues that realizing conditions of individual autonomy can serve as the cut-off point to duties of global justice. I investigate his idea of autonomy, arguing that in order to make sense of this claim, we need a concept of autonomy. I propose 4 possible definitions of autonomy, none of which seem to necessitate Gilabert’s duties of egalitarian global justice. Instead, I propose that he may have in mind Autonomy 5, which requires that individuals have access to a maximum number of options and not simply a sufficient range of options to choose from. I criticize this premise as too demanding in the global world characterized by fundamental inequality. Second, I argue that if we were to endorse the preconditions for Autonomy 5, we would have to accept that Gilabert’s theory of global justice doesn’t provide for a cut-off point of duties of global justice.